"Still I Rise": a Black feminist teacher's journey to (re)member her journey to teach. Issue 4 (4th July 2021) - Vickery, Amanda E.
ABSTRACT: This critical autoethnography documents how the author navigated the dilemma of learning and teaching history as a racial queer. Through the use of narrative vignettes and reflection, the author examines how a woman of color social studies teacher educator (re)members the past as a way to inform her teaching of history? The first memory dealt with how public historical memory can be used as a weapon to maintain white supremacy. The second memory details how the author navigated the whiteness of teacher preparation and schools. The final memory documents how the author harnessed her cultural memories as a source of strength when teaching. Collectively, these narrative vignettes demonstrate the power of cultural memories and their potential to provide teachers of color with a source of strength within hostile school spaces.